2020
DOI: 10.1111/1756-185x.13879
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic arthritis: A systematic review of non‐HLA genetic studies and important signaling pathways

Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory disease that primarily invades the musculoskeletal system and skin. 1 Usually, besides the arthritis damage, including arthritis, enthesitis, dactylitis and axial involvement, patients with PsA have psoriatic skin, such as epidermal hyperplasia, hyperkeratosis, parakeratosis, Munro's microabscesses and mixed dermal infiltrates. 2 In general, the severity of a patient's joint symptoms is consistent with the severity of the skin lesions. 3 In some cases, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…Evidence from meta-analyses and observational studies supports an underlying bidirectional relationship between psoriasis and inflammatory bowel disease (IBD), although mechanisms remain unclear (11,12). Many factors, such as common genetic susceptibility loci, clinical course, and immunologic features, are shared by psoriatic diseases and IBD (5,(13)(14)(15)(16), and IBD was considered a subsequent extra-articular manifestation of PsA which should be specially monitored in PsA patients according to the previous studies. However, basic and observational studies are susceptible to confounding factors, such as demographics or environmental exposure (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from meta-analyses and observational studies supports an underlying bidirectional relationship between psoriasis and inflammatory bowel disease (IBD), although mechanisms remain unclear (11,12). Many factors, such as common genetic susceptibility loci, clinical course, and immunologic features, are shared by psoriatic diseases and IBD (5,(13)(14)(15)(16), and IBD was considered a subsequent extra-articular manifestation of PsA which should be specially monitored in PsA patients according to the previous studies. However, basic and observational studies are susceptible to confounding factors, such as demographics or environmental exposure (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Specific non-HLA PsA variants have been identified in GWAS studies, including in the IL12B, NOS2 and IFIH1 regions as reported in a systematic review published in 2015 ( 141 ). Several signaling pathways possibly implicated in the pathogenesis of PsA were presented in a recent systematic review published in 2020 ( 142 ).…”
Section: Discussionmentioning
confidence: 99%
“…As well as the association between HLA and PsA, there is evidence for the involvement of other non-HLA genes in the pathogenesis of the disease [23]. The first GWAS performed to identify genetic factors predisposing to PsA was carried out in 2008 [24].…”
Section: Non-hla Genetic Associations By Genome-wide Association Studiesmentioning
confidence: 99%
“…In summary, the results from GWAS and successive meta-analyses have identified around 30 susceptibility non-HLA genes associated with PsA. We include a list of reported genome-wide PsA loci in Table 1 from the following studies [23][24][25][26][27][28]30,31,33]. Some of these genes have been described to be shared with other related diseases, such as AS, inflammatory bowel disease (IBD), RA or systemic lupus erythematosus (SLE) (Figure 1), being the most prominent genes: ERAP1, ERAP2, IL23A, IL23R, REL, RUNX3, STAT4, TLR4, TNIP1, TRAF3IP2, TYK2.…”
Section: Non-hla Genetic Associations By Genome-wide Association Studiesmentioning
confidence: 99%